Improving Students’ Creative Poetry Writing Skills through the Discovery Inquiry Method - Ros Liana Tambak; Ridho Kurniawan; Endi Zunaedy Pasaribu (Program Studi Pendidikan Bahasa Inggris, Universitas Pendidikan Muhammadiyah Sorong, 2025)
This study aims to examine the effectiveness of the Discovery Inquiry method in improving students’ creative poetry writing skills among eighth-grade students at SMP Negeri 1 Silangkitang. The research employed a Classroom Action Research (CAR) design consisting of four stages: planning, implementing actions, observing, and reflecting. The participants were 25 students from class VIII. Data were collected through classroom observations, student interviews, and analysis of students’ poetry. The results show that the Discovery Inquiry method significantly enhanced students’ performance in writing poetry. The average score increased from 68.4 in the first cycle to 86.2 in the second cycle, marking a 26% improvement. Students showed notable progress in creativity, word choice accuracy, and mastery of poetic structure. Moreover, their self-confidence, critical thinking ability, and willingness to experiment with language and poetic forms also improved. During the implementation, students became more engaged and active in the learning process, as they were encouraged to explore ideas and express emotions freely through poetry. The findings indicate that the Discovery Inquiry method not only develops technical writing skills but also nurtures creative expression and motivation to learn literature. Therefore, this method can be considered an effective and student-centered strategy for enhancing poetry writing skills and promoting creative learning in language and literature classes.